Examination of feral pigeon populations at animal breeding farms - Varga, Sándor; Juhász, Lajos (Acta Agraria Debreceniensis, 2007)
In the course of our examination, we assessed biometric data that determine gender, we evaluated sexual activity, measured the nourishment and necropsies of two feral pigeon populations feeding and nesting at animal breeding farms. The changes in the body weight of the different genders were significant on both farms (p<0.05). The body weight and the crop volume of the birds were not significantly different at the examined farms. On both farms, the elemental food source of the birds was the fodder and corn kernels given to cattle, and was supplemented by that of the pigeons living at the Debrecen farm with food from surrounding farms and with other seeds (pea, millet, rye). By the examination of the genitals, the birds collected from the Nyírbátor farm showed sexual activity from the beginning of spring, and in the summertime decreasing activity is characteristic, while the pigeons from the Debrecen farm are only active from the summer months. In the course of the examinations in the Veterinary Institute of Debrecen, the birds proved to be free of parasites and the results of the Newcastle disease analysis were negative as well. The bacteriologic analyses showed a different proportion of E.coli, Pasteurella multicoda, haemolysing Staphylococcus bacteria at the two cattle farms. During the examinations for the statement of Salmonellas, this causative agent was stated only in case of birds that spend nights and nested in the town, which allude to human origin. We demonstrated Eimeria oocysts during the parasitological examination of the fecal samples in 5 cases at the Debrecen, and in 1 case at the Nyírbátor farm.